EFFECT OF VENTILATORY MUSCLE TRAINING AND AEROBIC EXERCISE PROGRAM IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE ON RESPIRATORY FUNCTIONAL TEST AND ARTERIAL BLOOD GASES - Ülkü Sarpkaya; Hakan Tuna; Gündeniz Altıay; Erhan Tabakoğlu (Archives of Rheumatology, 2004)
The main aim of pulmonary rehabilitation is to improve life quality, strength and endurance; additionally prevent dyspnea as well. Our study designed for evaluation the effectiveness of pulmonary rehabilitation was conducted in 19 COPD patients (16/3 men/women) whose mean (SD) age was 61,00 (9,6) years and mean forced expiratory volume in one second (FEV1) was 1,46 (0,60). After completion of 6-8 weeks homebased threshold IMT ventilatory muscle training program, hospital-based 3 weeks intensive bicycle ergometer exercise training was conducted for each patient. There were statistically significant improvements in FEV1, forced vital capacity (FVC), maximum inspiratory-expiratory pressure (PImax- PEmax), arterial oxygen pressure and oxygen saturation (PO2, SaO2), 6 minute walk distance (p<0,05). These results confirm our thought that pulmonary rahabilitation could be separated confidently and additional benefits could be more powerful with preparing the respiratory system before aerobic exercise training.